The genus Pseudachorutes Tullberg, 1871 (Collembola, Neanuridae) in the Ukraine with descriptions of new species - Kaprus’, Ighor J.; Weiner, Wanda M. (Zootaxa, 2009)
Four new species of Pseudachorutes from Ukraine are described and illustrated: P. vitalii sp. nov., P. scythicus sp. nov., P. vasylii sp. nov. and P. janstachi sp. nov. These new species differ in the body size, in the details of body chaetotaxy, in the number of vesicles of PAO, in the shape of mandibles, in the chaetotaxy of labrum and labium. The following species are redescribed on the basis of Ukrainian material: Pseudachorutes pratensis Rusek, 1973, Pseudachorutes palmiensis Börner, 1903, Pseudachorutes parvulus Börner, 1901, Pseudachorutes subcrassus Tullberg, 1871, Pseudachorutes dubius Krausbauer, 1898 and Pseudachorutes corticicolus (Schäffer, 1896). A key to the Ukrainian Pseudachorutes species are given, too.